HUBUNGAN POWER OTOT LENGAN BAHU DAN POWER OTOT TUNGKAI DENGAN KETERAMPILAN JUMP SMASH PADA CLUB BADMINTON PUTRA PB. BANK RIAU KEPRI PEKANBARU - R Siallagan, Riswan; ', Ramadi; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrack: The problem of this research is a lack of skills jump smash in badminton men's club PB. Bank Riau kepri Pekanbaru. It is estimated because of the lack of shoulder arms muscle and leg’s muscle power at the time of the jump smash. The purpose of this study is to determine the relationship of the shoulder arms muscle and leg’s muscle power with jump smash skill. This study is correlational which aims to find out the relationship between independent and dependent variables. After that, the test of normality data used Liliefors test with the significance level α = 0.05 and the results of normality test obtained variable X1, L0max (0.2422) <Ltabel (0.258), and the results of normality test variable X2, L0max (0.1292) <Ltabel (0.258), the normality test variable Y, L0max (0.1594) <Ltabel (0.258), in other words the data distributed normally. Then continued by determining r used correlation analysis product moment, if thitung>ttabel so there is a significant relationship. From the calculation of the correlation between shoulder arms muscle with jump smash skill acquired rhitung = 0.794 while the rtable=0.666 The results of calculation of correlation between leg’s muscle power with a jump smash skills acquired rhitung = 0.739 while the rtable= 0.666. To determine the variables R X1 and X2, the Y performed using double correlation formula, with rhitung (0.840)> rtabel (0.666). So Ho rejected and Ha accepted. Thus the conclusion there is a significant correlation shoulder arms muscle and leg’s muscle power at the time of the jump smash in men’s badminton club of PB. Bank Riau Kepri Pekanbaru.Key Words : Shoulder arms muscle , Leg’s muscle power , Jump smash